Synthesis And Characterization of Novel Functionalized Tetradentate Ligand Type H3NS3 And Its Metal Complexes With Re(V), Ni(II), Cu(II), Cd(II) & Hg(II) - Kanan M. Tawfiq; Mohamad J. Al-Jeboori; Matheel D. Al-Sabti (Engineering and Technology Journal, 2010)
This work represents the preparation of the tetradentate ligand H3NS3 (H3L) andits metal complexes with rhenium(V), nickle(II), copper(II), cadmium(II) andmercurry(II) metal ions. The ligand and its complexes were characterized when neededby Infrared, Ultraviolet–visible, HPLC, Mass, 1H nuclear magnetic resonance, andatomic absorption spectroscopic techniques, elemental analysis, and electricalconductivity. The proposed structure for (H3NS3) with Re(V) is square pyramidal, withNi(II) is distorted square planar, and with the rest of metal ions is distorted tetrahedral